Associated factors of mortality in first-ever stroke patients - Mustafa, Mamat; Wan Arfah Nadiah, Wan Abdul Jamil; Mustapha, Muzaimi (Asian Research Publishing Network, 2015)
The aim of this study was to determine the associated factors of mortality in first-ever stroke patients receiving care in a suburban hospital setting in Malaysia. A retrospective record review study was conducted among 432 first-ever stroke patients in Hospital Universiti Sains Malaysia, Kelantan, Malaysia. Information on demographic characteristics, past medical history, clinical characteristics, medications prior to stroke and symptoms and signs of first-ever stroke patients were retrieved from medical records. Multiple logistic regression was used for data analysis. At the study endpoint, 101 (23.4%) death was identified and 331 patients (76.6%) were still alive till data collection was completed. The significant prognostic factors included male, patients with seizure/ fit, marital status, Glasgow coma scale score, fasting blood sugar, smoking status, patients with rheumatic heart disease, level of urea and patients with subarachnoid haemorrhage. The findings of this study highlighted the key clinical parameters of associated factors of mortality in first-ever stroke patients in a predominantly suburban setting in Malaysia.